ANALISA VARIABEL YANG MEMPENGARUHI KINERJA KERJA KARYAWAN PT. MANUNGGAL MAJU JAYA - Rudi Yanto Batara Silalahi; Rimayang Anggun Laras Prastianty Ramli (BENING, 2021)
Work performance is the output of the work of its members in achieving the goals of an organization. Because the performance variable is so important, there are many other variables that affect the performance, one of which is personality, work environment and communication. So this study aims to determine the effect of personality, work environment and communication on work performance. This study used all employees of PT. Manunggal Maju Jaya as a sample. Furthermore, data analysis in this study using SmartPls version 2.0 software. Where the results of the study show that there is a significant effect of each personality variable and work environment on work performance, while the communication variable does not have a significant effect on work performance